2009
DOI: 10.1016/j.seizure.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Conversation analysis can help to distinguish between epilepsy and non-epileptic seizure disorders: A case comparison

Abstract: This study illustrates the importance of the time point at which patients share information with the doctor. It supports the notion that close attention to how patients communicate can help in the differential diagnosis of seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Research initially carried out in Germany but then also in the United Kingdom and elsewhere showed that patients with epilepsy tend to focus on their subjective seizure experiences and expend considerable effort to explain exactly how they feel in their seizures; in contrast, those with PNES preferentially focus on the circumstances in which their seizures occurred or the consequences of their seizures [50][51][52][53]. The metaphoric conceptualisations of seizure experiences preferred by patients with epilepsy place the linguistic agency with the seizure, which acts independently and often in a hostile fashion (eg.…”
Section: Interactional Representationmentioning
confidence: 99%
“…Research initially carried out in Germany but then also in the United Kingdom and elsewhere showed that patients with epilepsy tend to focus on their subjective seizure experiences and expend considerable effort to explain exactly how they feel in their seizures; in contrast, those with PNES preferentially focus on the circumstances in which their seizures occurred or the consequences of their seizures [50][51][52][53]. The metaphoric conceptualisations of seizure experiences preferred by patients with epilepsy place the linguistic agency with the seizure, which acts independently and often in a hostile fashion (eg.…”
Section: Interactional Representationmentioning
confidence: 99%
“…T grounded in the qualitative methodology of Conversation Analysis (CA) [17][18][19], identified two contrasting conversational profiles which were closely linked to patients' medical diagnoses: whereas patients with epilepsy were likely to volunteer detailed talk about subjective seizures symptoms, patients with PNES tended to avoid symptom descriptions and to focus on the circumstances or consequences of their seizures [20]. In later studies linguists were shown to be able to use these features accurately to predict a is [21], with linguistic raters correctly predicting 85% of diagnoses subsequently confirmed by video-EEG. In contrast, only 40% of the working diagnoses formulated by the ior to admission were supported by the video-EEG findings [21].…”
Section: Previous Linguistic and Interactional Findingsmentioning
confidence: 99%
“…In later studies linguists were shown to be able to use these features accurately to predict a is [21], with linguistic raters correctly predicting 85% of diagnoses subsequently confirmed by video-EEG. In contrast, only 40% of the working diagnoses formulated by the ior to admission were supported by the video-EEG findings [21]. However, it has also been shown that the conversational features which the linguistic raters used to make their diagnostic predictions require doctors to adopt the unusually open style of questioning used in the original research studies.…”
Section: Previous Linguistic and Interactional Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two contrasting conversational profiles matching patients' medical diagnoses emerged: whereas patients with epilepsy were likely to volunteer detailed talk about subjective seizures symptoms, patients with NES tended to avoid symptom descriptions and instead focus on the circumstances or consequences of their seizures (Schwabe et al, 2008). The incomplete seizure narratives and inability or unwillingness to topicalize seizure symptoms typical of NES patients (rather than a preferred focus on the situations in which seizures occur or the consequences of seizures) become particularly clear when they are prompted to speak about particularly memorable seizure episodes such as their first, last or worst seizure (for an exemplary case comparison see Plug et al, 2009). These findings do not seem language dependent: having initially been noted in German speaking patients (Schwabe et al, 2008), they have been replicated in clinical encounters with Italian speakers (Cornaggia et al, 2012).…”
Section: Linguistic Features Can Be Used To Distinguish Between Epilementioning
confidence: 99%